Memahami Fungsi Setiap Unsur Dalam Budaya Tinju Adat (Sudu) Masyarakat Zepe, Ngada, Menurut Perspektif Antropologi Budaya Ralph Linton - Sekundus Septo Pigang Ton; Yoseph Edelbertus Dua; Hilarion Gerri Parto; Fransiskus Antonius Dimas Satyawardhana; Raymundus I Made Sudhiarsa (CV. Multi Kreasi Media, 2024)
The focus of this paper is to understand the function of each element in the customary boxing culture (Sudu) of the Zepe community, Ngada, from the perspective of Ralph Linton's cultural anthropology. Sudu (customary boxing) in Ngada society is a tradition of boxing matches that has a function as a relationship in strengthening social ties between individuals. The purpose of this paper is to understand the function of each element in Ngada people's sudu culture that has social meaning and value. The findings are that sudu is a culture that has been passed down from generation to generation and has the function of mutual respect and brotherhood. In addition to these functions, sudu also has a deep meaning for survival and social relations. The sudu ceremony reflects harmonious relations and friendship through sportsmanship between boxers, as well as solidarity between lives in the Ngada community. Sudu is not only a physical fight, but also a medium to express courage, honor and traditional values. Furthermore, the nelo (dance) that accompanies sudu serves as a cultural expression that strengthens identity and social bonds. The methods used in writing this paper are literature studies and interviews with a descriptive-analytical approach.